Quantitative genomic analysis of agroclimatic traits in sorghum - Olatoye, Olalere Marcus (Kansas State University, 2017)
Climate change has been anticipated to affect agriculture, with most the profound effect in regions where low input agriculture is being practiced. Understanding of how plants evolved in adaptation to diverse climatic conditions in the presence of local stressors (biotic and abiotic) can be beneficial for improved crop adaptation and yield to ensure food security. Great genetic diversity exists for agroclimatic adaptation in sorghum (Sorghum bicolor L. Moench) but much of it has not been characterized. Thus, limiting its utilization in crop improvement. The application of next-generation sequencing has opened the plant genome for analysis to identify patterns of genome-wide nucleotide variations underlying agroclimatic adaptation. To understand the genetic basis of adaptive traits in sorghum, the genetic architecture of sorghum inflorescence traits was characterized in the first study. Phenotypic data were obtained from multi-environment experiments and used to perform joint linkage and genome-wide association mapping. Mapping results identified previously mapped and novel genetic loci underlying inflorescence morphology in sorghum. Inflorescence traits were found to be under the control of a few large and many moderate and minor effect loci. To demonstrate how our understanding of the genetic basis of adaptive traits can facilitate genomic enabled breeding, genomic prediction analysis was performed with results showing high prediction accuracies for inflorescence traits. In the second study, the sorghum-nested association mapping (NAM) population was used to characterize the genetic architecture of leaf erectness, leaf width, and stem diameter. About 2200 recombinant inbred lines were phenotyped in multiple environments. The obtained phenotypic data was used to perform joint linkage mapping using ~93,000 markers. The proportion of phenotypic variation explained by QTL and their allele frequencies were estimated. Common and moderate effects QTL were found to underlie marker-trait associations. Furthermore, identified QTL co-localized with genes involved in both vegetative and inflorescence development. Our results provide insights into the genetic basis of leaf erectness and stem diameter in sorghum. The identified QTL will also facilitate the development of genomic-enable breeding tools for crop improvement and molecular characterization of the underlying genes Finally, in a third study, 607 Nigerian accessions were genotyped and the resulting genomic data [about 190,000 single nucleotide polymorphisms (SNPs)] was used for downstream analysis. Genome-wide scans of selection and genome-wide association studies (GWAS) were performed and alongside estimates of levels of genetic differentiation and genetic diversity. Results showed that phenotypic variation in the diverse germplasm had been shaped by local adaptation across climatic gradient and can provide plant genetic resources for crop improvement.
Keywords: Quantitative; Agroclimatic; Genomic Analysis; Sorghum; Clinal Adaptation; Nested Association Mapping